Murine Cytomegalovirus Infection Induces Susceptibility to EAE in Resistant BALB/c Mice - Milovanovic, Jelena; Popovic, Branka; Milovanovic, Marija; Kvestak, Daria; Arsenijevic, Aleksandar; Stojanovic, Bojana; Tanaskovic, Irena; Krmpotic, Astrid; Arsenijevic, Nebojsa; Jonjic, Stipan; Lukic, Miodrag L. (Frontiers in Immunology, 2017)
In contrast to C57BL/6 mice, BALB/c mice are relatively resistant to the induction of experimental autoimmune encephalomyelitis (EAE) after challenge with MOG35–55 peptide. Here, we provide the first evidence that infection with murine cytomegalovirus (MCMV) in adulthood abrogates this resistance. Infected BALB/c mice developed clinical and histological signs similar to those seen in susceptible C57BL/6 mice. In addition to CD4+ cells, large proportion of cells in the infiltrate of diseased BALB/c mice was CD8+, similar with findings in multiple sclerosis. CD8+ cells that responded to ex vivo restimulation with MOG35–55 were not specific for viral epitopes pp89 and m164. MCMV infection favors proinflammatory type of dendritic cells (CD86+CD40+CD11c+) in the peripheral lymph organs, M1 type of microglia in central nervous system, and increases development of Th1/Th17 encephalitogenic cells. This study indicates that MCMV may enhance autoimmune neuropathology and abrogate inherent resistance to EAE in mouse strain by enhancing proinflammatory phenotype of antigen-presenting cells, Th1/Th17, and CD8 response to MOG35–55.